Physical and Mechanical Properties of Superior “Mega” and Conventional Teak Wood Planted in Wanagama Educational Forest, Gunungkidul, Yogyakarta - Fanny Hidayati; Isti Tamira Fajrin; Muhammad Rosyid Ridho; Widyanto Dwi Nugroho; Sri Nugroho Marsoem; Mohammad Na'iem (Jurnal Ilmu Kehutanan)
Demand of teak wood increases every year along the increase of human population and prosperity. On the other hand, teak is one of the long rotation tree species. Furthermore, the avaibility of teak from the Perum Perhutani as the biggest teak plantation company is not enough to fulfill the demand of teak wood from wood industry. Therefore, many efforts have been conducted to solve this problem, such as by tree breeding program. In Indonesia, this program only focused in the growth characteristics. However, information of wood properties of superior teak is still limited in Indonesia. Therefore, the aim of this research was to clarify the physical and mechanical characteristics of superior teak wood (11-year-old) and compared with the conventional teak (14-year-old) planted in Wanagama Forest, Gunungkidul, Yogyakarta and its longitudinal variation. As the results, physical properties were not significantly different between superior teak and conventional teak, except for green moisture content. Bending strength (MOR dan MOE) and compression strength parallel to grain were significantly different between superior and conventional teak. In addition, compressive strength perpendicular to grain was not significantly different between superior and conventional teak.